RAILWAYS AND THE RAJ : HOW THE AGE OF STEAM TRANSFORMED INDIA - CHRISTIAN WOLMAR (LONDON ATLANTIC BOOKS, 2017)
The epic story of the British construction of the railways in India, as told by Britain's bestselling transport historian
Keywords: RAILWAYS; BRITISH INDIA